Failures in crisis communication during the Covid-19 pandemic in Slovenia - Kamin, Tanja (Teorija in praksa, 2021)
During a pandemic, it is essential that most people respect the measures in place so as to keep the health crisis at bay. Still, a consensus must exist in society that the measures imposed by government are truly needed, just and legitimate, with several factors affecting whether this is achieved. In the article, we present the results of qualitative research (23 in-depth interviews) conducted in Slovenia at the peak of the first lockdown, focusing on how the study participants (women who were living alone during the first lockdown) perceived communication from the government and the public health authorities that comprised the official crisis communication group for managing the pandemic in Slovenia. The results present critical mistakes in communication that shaped trust in the official communicators and failed to motivate and encourage respondents to comply with the recommended and prescribed protective measures.
Keywords: Covid-19; Crisis communication; Epidemics; Epidemije; Krizno komuniciranje; Samske ženske; Single women; Trust; Zaupanje